2021
DOI: 10.3390/ijerph18147595
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Predictors of Solid- and Hematological Malignancies in Patients with Giant Cell Arteritis: A Large Real-World Database Study

Abstract: Background: The association between giant cell arteritis (GCA) and malignancies had been widely investigated with studies reporting conflicting results. Therefore, in this study, we aimed to investigate this association using a large nationwide electronic database. Methods: This study was designed as a retrospective cohort study including GCA patients first diagnosed between 2002–2017 and age, sex and enrollment time-matched controls. Follow-up began at the date of first GCA-diagnosis and continued until first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The diagnoses are documented by either a primary care physician or specialist using the International Classification of Diseases (ICD). The data is systematically verified and was found to be highly creditable in previous studies (11,12), including study that investigated the association between FM and diabetes mellitus (13). The Ethics Committee of the CHS approved this study and waived the requirement for informed consent.…”
Section: Methodsmentioning
confidence: 52%
See 1 more Smart Citation
“…The diagnoses are documented by either a primary care physician or specialist using the International Classification of Diseases (ICD). The data is systematically verified and was found to be highly creditable in previous studies (11,12), including study that investigated the association between FM and diabetes mellitus (13). The Ethics Committee of the CHS approved this study and waived the requirement for informed consent.…”
Section: Methodsmentioning
confidence: 52%
“…Moreover, this study lacks information regarding temporality, and the information concerning the criteria for diagnosing the various diseases was unavailable. However CHS data are systematically verified and was found to has high validity in earlier studies (11)(12)(13).…”
Section: Discussionmentioning
confidence: 69%
“…A retrospective study reported a higher risk of solid malignancy (Hazard Ratio (HR) = 1.2) and hematological malignancy in GCA compared to a control population. Higher age at diagnosis and male gender were associated with malignancy [86]. By contrast, other studies did not confirm these results [87].…”
Section: Malignancymentioning
confidence: 71%
“…Ji et al and Muller et al found an increased risk of cancer within the first 6 to 12 months after the diagnosis of PMR and GCA in large-scale register-based studies ( 20 , 21 ). Similarly, Dar et al and Bellan et al both found an increased risk of cancer in patients with GCA and PMR, respectively, and both studies found that male sex and older age were independent predictors for malignancy ( 16 , 22 ). Conversely, other studies, such as those from Pfeifer et al and Hill et al have not been able to confirm a higher risk of malignancy in patients diagnosed with PMR/GCA ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 86%